Studi Perbandingan Hukum Ijarah dalam Perspektif Fikih Muamalah dan Hukum Positif - M. Ainun Imam; Khaerul Aqbar; Muh. Dzul Fadli S. (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine the comparison of law in the review of muamalah fiqh and positive law against ijarah law. This research is a library research with a normative juridical legal approach and a comparative approach, which discusses doctrines or principle in legal science wich is often called theoretical research, wich includes comparative legal research. The results showed that: (1) There is an equation in the definition that both are a contract to take or benefit an item with wages within a certain period of time, in the nature of the contract that is mutually binding on both parties and both have five pillars that must be fulfilled; (2) There is a difference in the source and foundation, that muamalah fiqh is based directly on the Qur'an and Hadith, who governs life in this world and the afterlife, while positive law comes from Pancasila. UUD, KUH Perdata, KUH Pidana, which is limited to regulating the peace of life in the world. Regarding the terms of ijarah, positive law mentions the maintenance of goods, that it is not allowed during the rental time to change the form or arrangement of the goods rented, while in muamalah fiqh does not discuss it on the terms of ijarah, but it has both good and bad effects. In positive law, leasing services is a separate discussion, called an employment agreement.